Preparation method and application of composite biological sludge dehydrating agent
Through the synergistic effect of the graded sol particles and the dynamic response polymer matrix, combined with water fracture additives, a composite biological sludge dehydration agent is prepared, which solves the problems of low sludge dehydration efficiency, poor adaptability and limited effect on combined water in the prior art, and achieves an efficient and deep sludge dehydration effect.
Patent Information
- Application Number
- CN202510114505.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The existing sludge dehydrating agents have poor results in complex sludge treatment scenarios, including low flocculation efficiency, poor adaptability, limited effect on bound water, and imperfect preparation technology.
The synergistic effect of graded sol particles and dynamic response polymer matrix is adopted, through the efficient combination of primary nanosol particles and organic matter in sludge, the bridge flocculation effect of secondary microsol particles on inorganic matter, and combined with the use of water fracture additives, a composite biological sludge dehydrating agent is formed.
The sludge dehydration efficiency and deep dehydration capacity are significantly improved, the dispersion, solubility and application effect of the dehydrating agent are optimized, and the shortcomings of traditional dehydrating agents in complex sludge treatment are solved.
Smart Images

Figure CN119612924A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sludge treatment, and in particular to a preparation method and application of a composite biological sludge dehydrating agent. Background Art
[0002] Sludge dewatering is an important part of sludge treatment and disposal. Its core purpose is to achieve efficient separation of water in sludge through the action of dewatering agents, reduce the moisture content of mud cakes, and provide a technical basis for subsequent transportation, treatment and resource utilization. At present, the sludge dewatering agents widely used in the market mainly include single polymer flocculants and inorganic coagulants. However, the application effects of these traditional dewatering agents in complex sludge treatment scenarios are often difficult to meet actual needs.
[0003] First, existing single polymer flocculants (such as polyacrylamide) have certain adsorption and flocculation capabilities in sludge dewatering, but their mechanism of action mainly depends on the electrostatic interaction with the surface of sludge particles and the bridging effect of molecular chains. Due to the complex composition of sludge particles, including organic matter, inorganic particles and other heterogeneous components, it is difficult for a single polymer dehydrating agent to take into account the characteristics of different particles, resulting in low efficiency and insufficient stability in the formation of floccules. At the same time, the structure of polymer flocculants is fixed, and it is difficult to achieve dynamic adaptation when the sludge composition or environmental conditions (such as pH, ionic strength) change. The flocculation effect is limited, and the dehydration efficiency fluctuates greatly. In addition, the effect of a single polymer dehydrating agent on bound water in sludge is limited, and it can only effectively remove free water and interstitial water. The deep dehydration capacity is obviously insufficient, and it is difficult to further reduce the moisture content of the mud cake.
[0004] Secondly, although traditional inorganic coagulants (such as aluminum salts and iron salts) have certain adsorption and sedimentation capabilities when treating sludge with high inorganic particle content, their effects are mainly concentrated on simple electrical neutralization between particles and lack an effective molecular chain bridging mechanism. Inorganic coagulants can easily lead to loose mud cake structure and poor compressibility, which ultimately affects the dehydration effect. In addition, the large amount of inorganic coagulants used can easily cause an increase in chemical residues in the sludge, high treatment costs, and the risk of secondary pollution. For complex sludge (such as high-organic matter sludge or high-oil sludge), the binding force between inorganic coagulants and particles is limited, and the treatment efficiency is significantly reduced.
[0005] Furthermore, the preparation process of traditional dehydrating agents also has significant deficiencies. High-temperature drying process is a commonly used method for preparing dehydrating agents, but this process easily destroys the active groups on the surface of particles or causes particle agglomeration, thereby significantly reducing the dispersibility and solubility of the dehydrating agent during actual use. The lack of process design to protect the microstructure and functional groups of particles makes the dehydrating agent unevenly distributed in the sludge, and the floc strength and stability are further reduced.
[0006] Therefore, the present invention proposes a preparation method and application of a composite biological sludge dehydrating agent to solve the deficiencies of the prior art. Summary of the invention
[0007] In view of the problems of low flocculation efficiency, poor adaptability, limited effect on bound water and imperfect preparation process in the existing technology of single polymer flocculants and inorganic coagulants in sludge dewatering, the present invention provides a preparation method and application of a composite biological sludge dewatering agent. The method significantly improves the sludge dewatering efficiency and deep dewatering capacity through the synergistic effect of scientifically designed graded sol particles and dynamically responsive polymer matrix, while optimizing the dispersibility, solubility and application effect of the dewatering agent.
[0008] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a composite biological sludge dehydrating agent comprises the following steps:
[0009] S1, preparing primary nano-sol particles, dispersing nano-silicon dioxide in deionized water, adding a cationic modifier for modification after ultrasonic dispersion, adjusting the pH value to alkaline, and stirring the reaction to obtain primary nano-sol particles;
[0010] S2, preparing secondary micron sol particles, dispersing aluminum oxide micron particles in deionized water, adding a surface modifier for coating reaction, and obtaining secondary micron sol particles;
[0011] S3, preparing a pH-sensitive polymer matrix, copolymerizing acrylamide and polyvinyl alcohol under the action of an initiator, and obtaining a pH-sensitive polymer matrix by introducing a functional monomer;
[0012] S4, mixing the primary nano-sol particles, the secondary micro-sol particles, and the pH-sensitive polymer matrix in proportion, stirring evenly, and adding a bound water fracture aid to form a composite sol system;
[0013] S5. Freeze-drying the composite sol system to obtain a composite sludge dehydrating agent.
[0014] Preferably, in the preparation of the primary nano-sol particles, the particle size of the nano-silica is 20-50 nm, the cationic modifier is tetramethyl quaternary ammonium salt, the pH value of the modification reaction is 9-10, the stirring speed is 300-500 rpm, and the reaction time is 1-2 hours.
[0015] The surface of nano-silica contains a large number of hydroxyl groups. Under alkaline conditions (pH 9-10), the surface hydroxyl groups can dissociate to form silanol anions, which improves its dispersion stability. Tetramethyl quaternary ammonium salt is a cationic modifier that fixes the cationic groups on the surface of nanoparticles through electrostatic adsorption and coupling, giving them positive charge. This positive charge not only enhances the adsorption capacity of nano-sol particles in the sludge system, but also improves its dispersibility in the composite sol system, making it easier to interact with organic matter on the surface of sludge particles.
[0016] Preferably, in the preparation of the secondary micron sol particles, the particle size of the aluminum oxide micron particles is 1-5 μm, the surface modifier is polyethyleneimine, the concentration of polyethyleneimine is 1%-5%, the reaction temperature is 50° C., and the reaction time is 1-2 hours.
[0017] The surface of alumina particles is rich in hydroxyl groups and exhibits weak cationicity in solution. By introducing polyethyleneimine (PEI), which contains rich amino and imine groups, it can bind to the surface of alumina particles through hydrogen bonds and coordination to form a stable coating. This coating not only improves the dispersion stability of the particles, but also enhances the flocculation and bridging ability of the particles, enabling them to better adsorb inorganic particles in the sludge. In addition, since the PE I molecule itself is weakly cationic, the electrostatic adsorption between it and the sludge particles further improves the overall dehydration efficiency.
[0018] Preferably, in the preparation of the pH sensitive polymer matrix, the mass ratio of acrylamide to polyvinyl alcohol is 4:1, the introduced functional monomer is acrylic acid, the amount of acrylic acid is 0.5%-2%, the polymerization temperature is 40-60°C, and the time is 4-6 hours.
[0019] Acrylamide provides a linear polymer structure, giving the polymer matrix good stretchability and adsorption properties; polyvinyl alcohol provides multi-point binding ability through its hydroxyl structure, enhancing the hydrophilicity and flexibility of the polymer matrix; the carboxyl group introduced by acrylic acid can undergo ionization behavior under different pH conditions, giving the polymer matrix good pH response characteristics. Under neutral or weakly alkaline conditions, the polymer chain segments expand to form a loose structure, which is conducive to capturing sludge particles; and during the filter press process, the pH-sensitive polymer can adaptively shrink and rearrange, thereby achieving efficient sludge dehydration.
[0020] Preferably, the mass ratio of the primary nano-sol particles, the secondary micro-sol particles and the pH-sensitive polymer matrix is 20%-30%: 15%-20%: 50%-60%, and the added amount of the bound water breaking aid is 5%-10%.
[0021] The primary nano-sol particles mainly target the organic matter particles in the sludge, forming a strong binding force with the organic matter through electrostatic adsorption; the secondary micro-sol particles target the inorganic matter in the sludge, and achieve a bridging effect through the coated cationic polymer layer; the pH-sensitive polymer matrix provides an overall network support, enhancing the adsorption and flocculation properties of the composite system. The bound water breaking aid (such as triethanolamine) destroys the stability of the bound water on the surface of the sludge particles through competitive hydrogen bonding, thereby improving the release efficiency of the bound water.
[0022] Preferably, the temperature range of the freeze-drying process of the composite sol system is -40°C to -60°C, and the freeze-drying time is 12-24 hours.
[0023] The freeze drying process can quickly remove the water in the sol system under low temperature, avoiding the damage of high temperature drying to the particle structure and functional groups, and retaining the dispersibility of the primary and secondary sol particles and the integrity of the pH-sensitive polymer. The powdered dehydrating agent is easy to be evenly distributed in the sludge system during actual use, ensuring good use effect.
[0024] Preferably, a composite biological sludge dehydrator is composed of the following components by mass percentage:
[0025] Primary nano-sol particles, accounting for 20%-30%;
[0026] Secondary micron sol particles, accounting for 15%-20%;
[0027] pH-sensitive polymer matrix, accounting for 50%-60%;
[0028] Combined water breaking aid, accounting for 5%-10%.
[0029] The dehydrating agent combines multiple action mechanisms: the electrostatic adsorption of organic matter by primary nano-sol particles, the bridging and flocculation of inorganic matter by secondary micron-sol particles, the pH-sensitive polymer matrix provides dynamic response capabilities to adapt to different sludge characteristics, and the water-breaking aid improves the water release efficiency through competitive action, ultimately achieving efficient sludge dehydration.
[0030] Preferably, the primary nano-sol particles are mainly composed of nano-silicon dioxide, have a particle size of 20-50 nm, and the cationic groups introduced on the surface are quaternary ammonium salt groups.
[0031] Preferably, the main component of the secondary micron sol particles is aluminum oxide, the particle size is 1-5 μm, and the surface coating material is polyethyleneimine; the pH sensitive polymer matrix is made of acrylamide and polyvinyl alcohol in a mass ratio of 4:1, and the functional groups introduced on the molecular chain are carboxyl and imidazole.
[0032] Preferably, the composite biological sludge dehydrating agent is used in sludge dehydration treatment, wherein the composite biological sludge dehydrating agent is added to the sludge at a ratio of 0.1%-0.3% of the sludge solid content, stirred evenly, and then dehydrated by plate and frame filter press or centrifugal equipment.
[0033] In sludge treatment, dehydrating agents achieve efficient dehydration through the following steps:
[0034] The primary and secondary sol particles combine with the organic and inorganic matter in the sludge, respectively, to form stable flocs;
[0035] The pH-sensitive polymer matrix dynamically regulates the conformation of the molecular chain, allowing the floccules to maintain high compressibility during the dehydration process;
[0036] The bound water breaking aid further releases the bound water in the sludge by breaking the hydrogen bonds between the sludge particles and water;
[0037] Finally, water and mud cake are effectively separated by filter pressing or centrifugation.
[0038] The present invention provides a preparation method and application of a composite biological sludge dehydrating agent, which has the following beneficial effects:
[0039] 1. The present invention adopts a technical solution of graded synergy of primary nano-sol particles and secondary micro-sol particles, and realizes comprehensive treatment of multiple components of sludge through efficient combination of nano-sol particles and organic particles in sludge, and bridging flocculation effect of micro-sol particles on inorganic particles. Compared with the limitations of single sol or polymer flocculants in the prior art, the problem of low treatment efficiency caused by the heterogeneity of sludge particles is overcome. This technology not only improves the adsorption and flocculation effects during sludge dehydration, but also significantly optimizes the dehydration rate, especially in complex sludge treatment scenarios containing a high proportion of organic or inorganic particles, showing stronger adaptability.
[0040] 2. The present invention introduces a pH-sensitive polymer matrix and utilizes the dynamic adjustment ability of polymer segments under different pH conditions, so that it can adaptively adjust the molecular conformation according to changes in the sludge system and enhance the flocculation effect. Due to the fixed structure of traditional polymer flocculants, the dehydration effect is often poor when the sludge composition fluctuates or the pH shifts. The dynamic response mechanism of the present invention can continuously optimize the structural strength and stability of the floccules and adapt to a variety of complex sludge conditions. In addition, the polymer matrix also cooperates with the sol particles to form a multi-level adsorption network, which greatly improves the consistency and efficiency of sludge treatment and solves the bottleneck problem of the difficulty in stable control of dehydration performance in traditional technologies.
[0041] 3. The present invention realizes the effective release of bound water in sludge through the application of bound water breaking aids. Bound water is difficult to remove by physical compression or ordinary flocculants due to hydrogen bonds or chemical bonds with the surface of sludge particles, and is a technical bottleneck for reducing the moisture content of mud cakes in traditional dehydration processes. The present invention introduces chemical additives with competitive binding ability into the sol system to accurately destroy the interaction force between sludge particles and bound water, thereby fundamentally solving the problem of bound water release. Compared with the limitation of the prior art that can only remove free water and interstitial water, the present invention can significantly reduce the final moisture content of the mud cake and exhibits superior technical performance in the field of deep sludge dehydration. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The present invention is a flow chart of the preparation method of the composite biological sludge dehydrating agent. DETAILED DESCRIPTION
[0043] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Please see attached Figure 1 :
[0045] Embodiment 1:
[0046] Preparation of primary nanosol particles
[0047] 10g nano silicon dioxide (particle diameter 30nm) is added into 100mL deionized water, uses ultrasonic treatment equipment (power 300W) to disperse 20 minutes under room temperature (25 ℃).In dispersion liquid, slowly drip tetramethyl quaternary ammonium salt solution (mass concentration 0.2%), keeping stirring velocity is 400rpm, and by dripping ammoniacal liquor, system pH value is adjusted to 9.5, reacts 1.5 hours simultaneously.Subsequently, gained one-level nano sol particle is left standstill and separated, standby.
[0048] Preparation of secondary micron sol particles
[0049] 15 g of aluminum oxide micron particles (particle size 3 μm) were weighed and added to 200 mL of deionized water, and stirred at 50° C. for 10 minutes using a magnetic stirrer to form a uniform suspension. Subsequently, 25 mL of polyethyleneimine solution (mass concentration 2%) was slowly added, and the stirring speed of the system was maintained at 350 rpm. The reaction was continued for 1 hour to obtain coated modified secondary micron sol particles.
[0050] Preparation of pH-sensitive polymer matrix
[0051] 40g acrylamide (AM) and 10g polyvinyl alcohol (PVA, molecular weight 90,000) were added to 200mL deionized water and slowly heated to 60°C to completely dissolve. 2g acrylic acid (AA) was added to the solution, and an initiator ammonium persulfate solution (concentration 0.3%, 10mL) was added dropwise under uniform stirring. The reaction was continued at 45°C for 4 hours to obtain a transparent pH-sensitive polymer matrix.
[0052] Assembly of composite sol system
[0053] Take 20mL of the first-level nanosol, 15mL of the second-level microsol and 50g of the pH-sensitive polymer matrix, mix them according to the proportion, stir at 400rpm, and stir for 1 hour. Then add the bound water breaking aid (such as triethanolamine, 10% solution, 6mL), and continue stirring at 40°C for 30 minutes to form a uniform composite sol system.
[0054] Freeze drying
[0055] The prepared sol system was injected into a freeze drying device, the freezing temperature was set to -50°C, and the drying time was set to 18 hours to obtain a composite biological sludge dehydrating agent powder.
[0056] The prepared dehydrating agent was added to the municipal sludge at a ratio of 0.2% of the sludge solid content, and after stirring for 5 minutes, it was dehydrated by a plate and frame filter press. The moisture content of the mud cake was finally reduced to 48%, which was significantly lower than the 60% of the traditional dehydrating agent, indicating that the present invention can effectively solve the problem of releasing bound water in sludge.
[0057] Embodiment 2:
[0058] Preparation of primary nanosol particles
[0059] 12 g of nano silicon dioxide (particle size 25 nm) was added to 120 mL of deionized water, and treated with an ultrasonic device of 350 W for 15 minutes at a temperature of 30° C. to form a uniform dispersion. Subsequently, 15 mL of tetramethyl ammonium salt solution (concentration 0.3%) was added, and the pH value was adjusted to 10 with ammonia water while stirring, and stirring was continued (rotation speed 350 rpm) for 1 hour to obtain a primary nano sol.
[0060] Preparation of secondary micron sol particles
[0061] Weigh 20g of aluminum oxide micron particles (particle size 4μm), add to 300mL of deionized water, heat to 55°C and stir for 20 minutes. Add 20mL of polyethyleneimine solution (concentration 1%), maintain stirring speed at 300rpm, react for 1 hour, cool and centrifuge to obtain modified secondary micron sol particles.
[0062] Preparation of pH-sensitive polymer matrix
[0063] 50 g acrylamide (AM) and 12 g polyvinyl alcohol (PVA) were added to 250 mL deionized water and dissolved in a 55°C water bath, followed by the addition of 3 g acrylic acid (AA) and 0.2% ammonium persulfate solution (8 mL). The mixture was stirred at 45°C for 5 hours to obtain a pH-sensitive polymer matrix with carboxyl and imidazole functions.
[0064] Assembly of composite sol system
[0065] 25 mL of the first-level nanosol, 20 mL of the second-level microsol and 50 g of the pH-sensitive polymer matrix were mixed in proportion, stirred at 450 rpm for 90 minutes, 8 mL of a 5% concentration triethanolamine solution was added, and stirred again for 45 minutes to prepare a composite sol system.
[0066] Freeze drying
[0067] The composite sol system is frozen to -60°C, dried for 24 hours, and crushed to obtain a powdered dehydrating agent with a particle diameter of 100-300 μm.
[0068] The dehydrating agent was used for industrial sludge (chemical sludge) at a dosage of 0.15%. The moisture content of the mud cake after sludge treatment was 46%, and the filtrate was clear during the filter press, indicating that the graded adsorption of the dehydrating agent solved the problem of uneven treatment of heterogeneous sludge particles.
[0069] Embodiment 3:
[0070] Preparation of primary nanosol particles
[0071] 8 g of nano-silica (particle size 40 nm) was added to 100 mL of deionized water and dispersed using a 300 W ultrasonic device for 30 minutes. Subsequently, 10 mL of 0.5% tetramethyl ammonium salt solution was added, the pH was adjusted to 9 with ammonia water, the stirring speed was 500 rpm, and the reaction was carried out for 2 hours to obtain primary nano-sol particles.
[0072] Preparation of secondary micron sol particles
[0073] Take 18g of aluminum oxide micron particles (particle size 2μm), disperse them in 250mL of deionized water, add 15mL of 2% polyethyleneimine solution at 45°C, stir (speed 300rpm) and react for 1.5 hours to obtain coated modified secondary micron sol particles.
[0074] Preparation of pH-sensitive polymer matrix
[0075] 35 g acrylamide (AM) and 15 g polyvinyl alcohol (PVA) were added to 200 mL deionized water and heated to 50° C. to dissolve. Subsequently, 2.5 g acrylic acid (AA) and 6 mL ammonium persulfate solution (concentration 0.4%) were added, and the reaction temperature was maintained at 40° C. for 6 hours to prepare a pH-sensitive polymer matrix with dynamic adjustment performance.
[0076] Assembly of composite sol system
[0077] 30 mL of the first-level nanosol, 20 mL of the second-level microsol and 50 g of the pH-sensitive polymer matrix were mixed and stirred (rotation speed 400 rpm) for 1 hour, and then 10 mL of a 5% triethanolamine solution was added and stirred for 30 minutes to form a composite sol system.
[0078] Freeze drying
[0079] The sol system is placed in a freeze dryer and frozen at -40°C for 18 hours, and a powdered composite sludge dehydrating agent is obtained after drying.
[0080] It is used for the treatment of high organic matter sludge (food wastewater sludge), with a dosage of 0.25%. The moisture content of the final mud cake is reduced to 47%, which is significantly better than the traditional polymer flocculant, fully demonstrating the advantages of the dehydrating agent of the present invention in treating bound water.
[0081] Comparative Example:
[0082] Comparative Example 1 (corresponding to Example 1, without using a cationic modifier)
[0083] Preparation of primary nanosol particles
[0084] 10g nano silicon dioxide (particle diameter 30nm) is added in 100mL deionized water, uses ultrasonic dispersion equipment (power 300W) to process 20 minutes. Directly stir subsequently, system pH value is adjusted to 9.5 (by adding ammoniacal liquor), continues stirring reaction 1.5 hours, obtains primary nano sol particles. This comparative example does not use cationic modifier tetramethyl quaternary ammonium salt.
[0085] The remaining steps
[0086] According to the steps in Example 1, secondary micron sol particles and pH sensitive polymer matrix were prepared, and the composite sol system was assembled and freeze-dried.
[0087] Comparative Example 2 (corresponding to Example 2, without using secondary micron sol particles)
[0088] Preparation of primary nanosol particles
[0089] According to the preparation method of primary nano-sol particles in Example 2, primary nano-sol particles were prepared using the same parameters.
[0090] The preparation step of the secondary micron sol particles is skipped, alumina micron particles and polyethyleneimine are not added, and the secondary sol particles are not coated.
[0091] Assembly of composite sol system
[0092] The primary nanosol and the pH-sensitive polymer matrix were directly mixed according to the proportion of Example 2 (the primary nanosol accounted for 25% of the total system), and a bound water breaking aid was added, stirred for 60 minutes and then freeze-dried.
[0093] Comparative Example 3 (corresponding to Example 3, the pH-sensitive polymer matrix does not introduce acrylic acid functional monomers)
[0094] Preparation of pH-sensitive polymer matrix
[0095] 35 g acrylamide (AM) and 15 g polyvinyl alcohol (PVA) were added to 200 mL deionized water and heated to 50° C. to dissolve. No acrylic acid (AA) was added as a functional monomer, and only 0.4% ammonium persulfate solution (6 mL) was added and stirred at 40° C. for 6 hours to obtain a common non-pH sensitive polymer matrix.
[0096] The remaining steps
[0097] According to the preparation method of the primary nano-sol particles and the secondary micro-sol particles in Example 3, the assembly of the composite sol system is consistent with the freeze-drying method.
[0098] Comparative Example 4 (corresponding to Example 1, the bound water breaking aid was not added)
[0099] Assembly of composite sol system
[0100] According to the steps in Example 1, the primary nano-sol particles, the secondary micro-sol particles and the pH-sensitive polymer matrix were mixed in proportion and stirred evenly. However, triethanolamine was not added as a bound water breaking aid, and the mixture was only stirred for 40 minutes before freeze drying to obtain a dehydrating agent powder.
[0101] Comparative Example 5 (corresponding to Example 2, freeze drying was changed to high temperature drying)
[0102] Freeze drying instead of high temperature drying
[0103] The composite sol system was prepared according to the steps in Example 2. The obtained sol system was transferred to a drying oven and dried at a constant temperature of 60° C. for 8 hours. During the drying process, the sol was regularly turned over to dehydrate evenly. Finally, a powdered dehydrating agent was obtained.
[0104] Comparative Example 6 (corresponding to Example 3, without using secondary nanosol and polymer matrix)
[0105] Using a single sol particle
[0106] Only the first-level nano-sol particle preparation method is used, and the second-level micro-sol particles and pH-sensitive polymer matrix are not added. The first-level nano-sol is directly used as the main component of the dehydrating agent, and the dehydrating agent is obtained by freeze drying.
[0107] Experiment 1: Effects of different sludge dehydrating agents on the moisture content of sludge cake
[0108] Experimental Description
[0109] Experimental steps:
[0110] Sludge sample preparation: Municipal sludge with a solid content of 4% was taken, stirred evenly and divided into three groups, with 500 g of sludge in each group.
[0111] Dehydrating agent addition:
[0112] Group 1: Add the dehydrating agent of Example 1 at a ratio of 0.2% of the sludge mass, stir at a speed of 200 rpm, and stir for 5 minutes.
[0113] The second group: the dehydrating agent of comparative example 1 (without the cationic modifier) was added, and the dosage and stirring conditions were the same as those of the first group.
[0114] The third group: the dehydrating agent of Comparative Example 4 (without the bound water breaking aid) was added, and the dosage and stirring conditions were the same.
[0115] Filter pressing and dehydration: The stirred sludge is transferred to a plate and frame filter press with a filtration pressure of 1.5 MPa and a filtration time of 10 minutes.
[0116] Mud cake collection and determination: Collect three groups of mud cakes, weigh them, and dry them in an oven at 105°C to constant weight, and calculate the moisture content (%) of the mud cakes.
[0117] Experimental data
[0118] Table 1 Effect of different sludge dehydrating agents on the moisture content of mud cake
[0119]
[0120] The dehydrating agent of Example 1 significantly reduced the moisture content of the mud cake, showing a stronger ability to remove bound water in the sludge. This effect is mainly attributed to the cationic modified primary nano-sol particles, which enhance the adsorption capacity of sludge particles through surface cationic groups. Especially under the condition that the surface of the sludge particles is negatively charged, the electrostatic adsorption of the primary sol particles plays a significant advantage and forms a tighter floc structure. In contrast, Comparative Example 1 did not use a cationic modifier, resulting in insufficient binding force between the sol particles and the sludge particles, and the dehydration effect is obviously weaker.
[0121] In the composite system of the present invention, the role of the bound water breaking aid is also crucial. Example 1 effectively destroys the hydrogen bonds between sludge particles and bound water by introducing competitive binding chemicals such as triethanolamine. This process is particularly critical for deep dehydration. Comparative Example 4 did not add a bound water breaking aid, which made it difficult to release the bound water in the sludge. Even if the filter pressure and time were the same, the moisture content of the mud cake was still high. This further proves the indispensability of bound water breaking aids in the deep dehydration process.
[0122] In addition, the superior performance of the dehydrating agent of Example 1 is also due to the synergistic effect of its multiple components. The cationic modified primary nanosol and secondary micron sol particles work together to construct a stable multi-stage flocculation network. The primary sol particles are responsible for the initial adsorption of organic particles in the sludge, and the secondary micron particles combine with the inorganic particles in the sludge through bridging flocculation, thereby forming a high-strength flocculent. However, Comparative Examples 1 and 4 lack key components, resulting in insufficient strength of the flocculation network structure, thereby affecting the effect of reducing the moisture content of the mud cake.
[0123] Experiment 2: Comparison of flocculation effects of dehydrating agents
[0124] Experimental Description
[0125] Experimental steps:
[0126] Sludge sample preparation: Take industrial sludge (chemical wastewater sludge, solid content 3%), stir it evenly and divide it into three groups, with 500g sludge in each group.
[0127] Dehydrating agent addition:
[0128] Group 1: The dehydrating agent of Example 2 was added in an amount of 0.15% of the sludge mass, the stirring speed was 300 rpm, and the stirring time was 3 minutes.
[0129] The second group: the dehydrating agent of Comparative Example 2 (secondary micron sol particles were not used) was added, and the dosage and stirring conditions were the same.
[0130] The third group: the dehydrating agent of Comparative Example 6 (only primary nano-sol particles) was added, and the dosage and stirring conditions were the same.
[0131] Floc Observation:
[0132] Let it stand for 2 minutes and observe the distribution and formation of flocs.
[0133] The flocs were collected and the average particle size was measured using a particle analyzer.
[0134] Floc strength test:
[0135] The static load method is used to place the floccules under a pressure platform, apply different pressures, and record their rupture pressure (unit: Pa).
[0136] Experimental data
[0137] Table 2 Effect of different dehydrating agents on flocculation effect
[0138]
[0139] The dehydrating agent of Example 2 exhibits excellent flocculation effect, with larger floccules and better distribution uniformity than other comparative groups. The secondary micron sol particles provide a key bridging effect in the flocculation process, and significantly enhance the structural strength of the floccules by combining with inorganic particles in the sludge. In contrast, comparative example 2 does not use secondary micron sol particles, and the stability of the flocculation network is affected, resulting in a significant reduction in the particle size of the floccules, uneven distribution, and a significant reduction in the overall flocculation effect.
[0140] In the composite system of the present invention, the primary nano-sol particles mainly target organic matter in the sludge and achieve efficient bonding through electrostatic adsorption; while the secondary micron particles supplement the deficiencies of the primary sol and provide stronger flocculation and adsorption capabilities for inorganic particles. The synergistic effect of this graded sol system constructs a multi-scale flocculation network, thereby effectively improving the strength and stability of the floccules. Comparative Example 6 only uses primary nano-sol particles and fails to form a complete composite flocculation system. The floccules have the smallest particle size and their strength is significantly lower than that of the embodiment.
[0141] In addition, the surface coating technology of the secondary micron sol particles in Example 2 further optimizes its performance. After the polyethyleneimine modification, the adsorption capacity of the micron particles is enhanced, and they are more tightly bound to the sludge particles, thus building a more stable flocculation network. However, due to the lack of this component in Comparative Example 2, the structure of the flocs is looser, and the rupture pressure is significantly lower, showing the problem of easy disintegration of the flocs during the dehydration process. The multi-component composite system of Example 2 effectively solves the technical difficulties of unstable flocculation effect and insufficient floc strength in the prior art.
[0142] Experiment 3: Verification of the ability to release water
[0143] Experimental Description
[0144] Experimental steps:
[0145] Sludge sample preparation: Take high-organic sludge (food processing wastewater sludge, solid content 3%), stir it evenly and divide it into three groups, with 500g of sludge in each group.
[0146] Dehydrating agent addition:
[0147] Group 1: The dehydrating agent of Example 3 was added at a ratio of 0.25% of the sludge mass, with a stirring speed of 250 rpm and a stirring time of 5 minutes.
[0148] The second group: the dehydrating agent of comparative example 3 (the pH-sensitive polymer matrix does not introduce acrylic acid functional monomer) was added, and the dosage and stirring conditions were the same as those of the first group.
[0149] The third group: the dehydrating agent of Comparative Example 4 (without the bound water breaking aid) was added, and the dosage and stirring conditions were the same.
[0150] Centrifugal separation: After stirring, the three groups of sludge samples were transferred to the centrifuge equipment respectively and centrifuged at 4000 rpm for 10 minutes to separate the mud cake and the supernatant.
[0151] Determination of bound water content:
[0152] The mud cake was collected and the bound water content (the percentage of bound water in total water) in the mud cake was measured by an infrared moisture analyzer (using the TGA method).
[0153] Determination of moisture content of mud cake: Using the standard drying method, the mud cake was dried at 105°C to constant weight, and the moisture content of the mud cake was calculated.
[0154] Experimental data
[0155] Table 3 Effect of different dehydrating agents on the release of sludge bound water
[0156]
[0157]
[0158] The dehydrating agent of Example 3 shows obvious advantages in bound water release performance, with the lowest percentage of bound water in the mud cake, which is significantly better than the two comparative groups. This effect is mainly attributed to the key role of the bound water breaking aid. Breaking aids such as triethanolamine competitively bind to the hydroxyl groups and hydrogen bonds on the surface of the sludge particles, effectively destroying the stable structure of bound water, thereby accelerating the release of bound water. In contrast, comparative example 4 did not use a bound water breaking aid. Even after centrifugal separation, the percentage of bound water in its mud cake was still high, and the effect of deep dehydration could not be achieved.
[0159] In addition, the pH-sensitive polymer matrix in the present invention also plays an important role in the release of bound water. Example 3 introduces acrylic acid functional monomers to enable the polymer to have dynamic response capabilities, which can adjust the conformation of the molecular chain during sludge treatment and improve the separation efficiency of interstitial water and bound water in sludge particles. However, the polymer matrix of Comparative Example 3 lacks pH sensitivity and has a relatively fixed molecular chain structure, resulting in limited auxiliary effects on the release of bound water and a higher moisture content in the final mud cake. This further verifies the key contribution of the polymer functionalization design of the present invention to the deep dehydration of sludge.
[0160] More importantly, the dehydrating agent of Example 3 forms a multiple adsorption and chemical bonding network under the synergistic effect of the graded sol particles and the bound water breaking aid. The primary nano-sol particles efficiently adsorb organic sludge, and the secondary micron sol particles enhance the overall stability through bridging flocculation, and further cooperate with the bound water breaking aid to completely break the bonding network of bound water. This composite system not only significantly improves the release capacity of sludge bound water, but also solves the limitation that traditional dehydrating agents can only act on free water and interstitial water, achieving a higher dehydration depth.
[0161] Experiment 4: Verification of the dispersibility and solubility of the dehydrating agent
[0162] Experimental Description
[0163] Experimental steps:
[0164] Sludge sample preparation: Take municipal sludge with a solid content of 4%, stir it evenly and divide it into two groups, with 500g of sludge in each group.
[0165] Dehydrating agent addition:
[0166] Group 1: The dehydrating agent (prepared by freeze drying) of Example 2 was added at a ratio of 0.2% of the sludge mass.
[0167] The second group: the dehydrating agent of comparative example 5 (prepared by high temperature drying) was added, and the dosage was the same as that of the first group.
[0168] Stirring process: Stir the two groups of sludge at 200 rpm for 3 minutes respectively, and observe the dissolution and dispersion of the dehydrating agent in the sludge.
[0169] Dispersibility determination:
[0170] After standing for 1 minute, the particle analyzer was used to detect the distribution uniformity and particle size range of the dehydrating agent particles in the sludge mixture.
[0171] Solubility determination:
[0172] The time required for the dehydrating agent to completely dissolve was recorded by microscopic observation (unit: seconds), and the effects of the two drying processes on the dissolution rate were compared.
[0173] Experimental data
[0174] Table 4 Effect of different drying processes on the dispersibility and solubility of dehydrating agents
[0175]
[0176] The solubility of the dehydrating agent in Example 2 is significantly better than that in Comparative Example 5, which is directly due to the protective effect of the freeze-drying process on the structural integrity of the sol particles. During the freeze-drying process, the water directly sublimates under low temperature conditions, avoiding the destruction of the primary nanosol and secondary micron sol particles under high temperature conditions, and retaining the active sites and functional groups on the particle surface. However, Comparative Example 5 uses high-temperature drying, and due to the effect of thermal stress, the dispersibility and solubility of the sol particles are significantly affected, and the particles dissolve slowly in the sludge and are unevenly distributed.
[0177] In addition, the multi-stage sol particles of the present invention form a loose microstructure under freeze-drying conditions, which is more easily dispersed in the sludge aqueous solution. The experiment of Example 2 shows that the dehydrating agent particles can be dissolved and evenly distributed in a relatively short time, while the particles after high-temperature drying in Comparative Example 5 show obvious dissolution hysteresis due to the partial destruction of the surface active groups. This hysteresis not only affects the initial flocculation effect of the dehydrating agent, but also leads to uneven formation of flocs during sludge treatment.
[0178] At the same time, the freeze-drying process plays a key role in preserving the composite structure of the multi-component system. The dehydrating agent of Example 2 disperses rapidly in the sludge, forming a stable multi-stage adsorption and flocculation network. This synergy enhances the overall efficiency of the dehydrating agent. In Comparative Example 5, due to high-temperature drying, partial agglomeration occurred between the particles, destroying the composite structure, and ultimately showing a lower distribution uniformity score. The results show that the freeze-drying process of the present invention not only optimizes the physical properties of the dehydrating agent, but also significantly improves its adaptability and effectiveness in practical applications.
[0179] Experiment 5: Processing cost comparison
[0180] Experimental Description
[0181] Experimental steps:
[0182] Sludge sample preparation: Municipal sludge (solid content 3%) and industrial sludge (chemical wastewater sludge, solid content 5%) were selected, stirred evenly, and then divided into three groups, with 500 g of sludge in each group.
[0183] Dehydrating agent addition:
[0184] Group 1: The dehydrating agent of Example 1 was added at a ratio of 0.2% of the sludge mass.
[0185] The second group: the dehydrating agent of comparative example 1 (without the cationic modifier) was added, and the dosage and stirring conditions were the same as those of the first group.
[0186] The third group: adding traditional polymer flocculant (polyacrylamide, conventional product) at a dosage of 0.4%.
[0187] Stirring and filter pressing:
[0188] Each group was mixed at 200 rpm for 5 minutes.
[0189] Transfer to a plate and frame filter press, filter at a pressure of 1.5 MPa and a filtration time of 10 min, and record the consumables and processing time required during the filtration process.
[0190] Cost calculation:
[0191] Record the usage of each group of dehydrating agents (unit: g), and calculate the cost of the agent for treating 500g of sludge (unit: yuan) based on the market price.
[0192] Record the time required for sludge dehydration and calculate the overall treatment efficiency (unit: minutes / kg sludge).
[0193] Experimental data
[0194] Table 5 Effect of different dehydrating agents on sludge treatment cost
[0195]
[0196] The dehydrating agent of Example 1 shows obvious advantages in treatment cost and efficiency, with lower dosage and shorter treatment time. The cationic-modified primary nano-sol particles show strong adsorption capacity in the sludge treatment process, and are more efficiently combined with the surface of sludge particles, thereby reducing the amount of dehydrating agent used. In Comparative Example 1, no cationic modifier was used, resulting in insufficient adsorption of the sol particles, reduced flocculation effect of the sludge particles, and a longer filter press process was required to achieve a similar treatment effect. Compared with traditional polymer flocculants, the dehydrating agent of Example 1 is significantly reduced in dosage, reflecting the economy and adaptability of the composite system.
[0197] On the other hand, the dosage of the traditional polymer flocculant in this experiment is twice that of the present invention, but its filtration time is not significantly shortened. This reflects the efficiency bottleneck of traditional products in treating complex sludge. The secondary micron sol particles in Example 1 construct high-strength floccules through bridging, and cooperate with the primary nanoparticles to form a stable multi-level network. This mechanism greatly optimizes the sludge dewatering process and fundamentally solves the problem of traditional technology that requires increasing the dosage to make up for insufficient flocculation.
[0198] In addition, the composite dehydrating agent of the present invention benefits from the introduction of the bound water breaking aid, and has a significant effect in releasing bound water. The effect of the bound water breaking aid in Example 1 not only accelerates the separation of free water and interstitial water, but also reduces the energy consumption of sludge dehydration, thereby further reducing the overall treatment cost. Compared with the high drug consumption and energy consumption of traditional flocculants, the dehydrating agent of Example 1 is more suitable for deep dehydration of industrial and municipal sludge, and its high efficiency and low cost provide a better solution for sludge treatment.
[0199] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a composite biological sludge dehydrating agent, characterized in that: The following steps are involved: S1, preparing primary nano-sol particles, dispersing nano-silicon dioxide in deionized water, adding a cationic modifier for modification after ultrasonic dispersion, adjusting the pH value to alkaline, and stirring the reaction to obtain primary nano-sol particles; S2, preparing secondary micron sol particles, dispersing aluminum oxide micron particles in deionized water, adding a surface modifier for coating reaction, and obtaining secondary micron sol particles; S3, preparing a pH sensitive polymer matrix, copolymerizing acrylamide and polyvinyl alcohol under the action of an initiator, and obtaining a pH sensitive polymer matrix by introducing a functional monomer; S4, mixing the primary nano-sol particles, the secondary micro-sol particles, and the pH-sensitive polymer matrix in proportion, stirring evenly, and adding a bound water fracture aid to form a composite sol system; S5. The composite sol system is freeze-dried to obtain a composite sludge dehydrating agent.
2. The method for preparing a composite biological sludge dehydrating agent according to claim 1, characterized in that: In the preparation of the primary nano-sol particles, the particle size of the nano-silicon dioxide is 20-50 nm, the cationic modifier is tetramethyl quaternary ammonium salt, the pH value of the modification reaction is 9-10, the stirring speed is 300-500 rpm, and the reaction time is 1-2 hours.
3. The preparation method and application of a composite biological sludge dehydrating agent according to claim 1, characterized in that: In the preparation of the secondary micron sol particles, the particle size of the aluminum oxide micron particles is 1-5 μm, the surface modifier is polyethyleneimine, the concentration of polyethyleneimine is 1%-5%, the reaction temperature is 50° C., and the reaction time is 1-2 hours.
4. The preparation method and application of a composite biological sludge dehydrating agent according to claim 1, characterized in that: In the preparation of the pH sensitive polymer matrix, the mass ratio of acrylamide to polyvinyl alcohol is 4:1, the introduced functional monomer is acrylic acid, the amount of acrylic acid is 0.5%-2%, the polymerization temperature is 40-60°C, and the time is 4-6 hours.
5. The preparation method and application of a composite biological sludge dehydrating agent according to claim 1, characterized in that: The mass ratio of the primary nano-sol particles, the secondary micro-sol particles and the pH-sensitive polymer matrix is 20%-30%: 15%-20%: 50%-60%, and the added amount of the combined water breaking aid is 5%-10%.
6. The preparation method and application of a composite biological sludge dehydrating agent according to claim 1, characterized in that: The temperature range of the freeze-drying process of the composite sol system is -40°C to -60°C, and the freeze-drying time is 12-24 hours.
7. A composite biological sludge dehydrating agent, characterized in that: It is composed of the following components by mass percentage: Primary nano-sol particles, accounting for 20%-30%; Secondary micron sol particles, accounting for 15%-20%; pH-sensitive polymer matrix, accounting for 50%-60%; Combined water breaking aid, accounting for 5%-10%.
8. The preparation method and application of a composite biological sludge dehydrating agent according to claim 1, characterized in that: The primary nano-sol particles are mainly composed of nano-silicon dioxide, with a particle size of 20-50 nm, and the cationic groups introduced on the surface are quaternary ammonium salt groups.
9. The preparation method and application of a composite biological sludge dehydrating agent according to claim 8, characterized in that: The main component of the secondary micron sol particles is aluminum oxide, the particle size is 1-5 μm, and the surface coating material is polyethyleneimine; the pH sensitive polymer matrix is made of acrylamide and polyvinyl alcohol in a mass ratio of 4:1, and the functional groups introduced on the molecular chain are carboxyl and imidazole.
10. Use of the composite biological sludge dehydrating agent according to claim 7 in sludge dehydration treatment, characterized in that: The composite biological sludge dehydrating agent is added to the sludge at a ratio of 0.1% to 0.3% of the solid content of the sludge, and after being stirred evenly, the sludge is dehydrated by plate and frame filter press or centrifugal equipment.
Citation Information
Patent Citations
Granulation and dehydration technology for dredged sludge
CN102311217A
Sewage treatment flocculant and preparation method thereof
CN112174280A
Modified nano silicon dioxide as well as preparation method and application thereof
CN114685076A
Efficient and economical sludge wall-breaking dehydrating agent and dehydrating method
CN115304238A
Use of nanoscale particles (nanoadditives) with cationic polymers to enhance conditioning and dewatering of sludge
US8303823B1